Activation of the Ca2+ "receptor" on the osteoclast by Ni2+ elicits cytosolic Ca2+ signals: evidence for receptor activation and inactivation, intracellular Ca2+ redistribution, and divalent cation modulation. - Shankar, V; Bax, C; Bax, B; Alam, A; Moonga, B; Simon, B; Pazianas, M; Huang, C; Zaidi, M (1993)
Earlier studies have demonstrated that a high (mM) extracellular Ca2+ concentration triggers intracellular [Ca2+] signals with a consequent inhibition of bone resorptive activity. We now report that micromolar concentrations of the divalent cation, Ni2+, elicited rapid and concentration-dependent elevations of cytosolic [Ca2+]. The peak change in cytosolic [Ca2+] increased monotonically with the application of [Ni2+] in the 50-5,000 microM range in solutions containing 1.25 mM-[Ca2+] and 0.8 mM-[Mg2+]. The resulting concentration-response function suggested Ni(2+)-induced activation of a single class of binding site (Hill coefficient = 1). The triggering process also exhibited a concentration-dependent inactivation in which conditioning Ni2+ applications in the range 5-1,500 microM-[Ni2+] inhibited subsequent responses to a maximally effective [Ni2+] of 5,000 microM. Ni(2+)-induced cytosolic [Ca2+] responses were not dependent on extracellular [Ca2+]. Thus, when 5,000 microM-[Ni2+] was applied to osteoclasts in Ca(2+)-free, ethylene glycol bis-(aminoethyl ether) tetraacetic acid (EGTA)-containing medium (< or = 5 nM-[Ca2+] and 0.8 mM-[Mg2+]), cytosolic [Ca2+] responses resembled those obtained in the presence of 1.25 mM-[Ca2+]. Prior depletion of intracellular Ca2+ stores by ionomycin prevented Ni(2+)-induced cytosolic [Ca2+] responses, suggesting a major role for intracellular Ca2+ redistribution in the response to Ni2+. The effects of Ni2+ were also modulated by the extracellular concentration of the divalent cations, Ca2+ and Mg2+. When these cations were not added to the culture medium (0 microM-[Ca2+] and [Mg2+]), even low [Ni2+] ranging between 5 pM and 50 microM elicited progressively larger cytosolic [Ca2+] transients. However, the response magnitude decreased at higher, 250-5,000 microM-[Ni2+], resulting in a "hooked" concentration-response curve. Furthermore, increasing extracellular [Mg2+] or [Ca2+] (0-1 mM) diminished the response to 50 microM-[Ni2+], a concentration on the rising phase of the "hook." Similar increases (0-10 mM) in extracellular [Mg2+] or [Ca2+] increased the response to 5,000 microM-[Ni2+], a concentration on the falling phase of the "hook". These findings are consistent with the existence of a membrane receptor strongly sensitive to Ni2+ as well as the divalent cations, Ca2+ and Mg2+. Receptor occupancy apparently activates intracellular Ca2+ release followed by inactivation. Furthermore, repriming is independent of intracellular Ca2+ stores, suggesting that such inactivation operates at a transduction step between receptor occupancy and intracellular Ca2+ release.